Teacher change beliefs: validating a scale with structural equation modelling - Kin, Tai Mei; Abdull Kareem, Omar; Nordin, Mohamad Sahari; Wai Bing, Khuan (School leadership & management, 2015)
The objectives of the study were to validate a substantiated Teacher Change Beliefs Model (TCBM) and an instrument to identify critical components of teacher change beliefs (TCB) in Malaysian secondary schools. Five different pilot test approaches were applied to ensure the validity and reliability of the instrument. A total of 936 teachers from 47 high-performing secondary schools completed the survey. Structural equation modelling was applied to test the models. Exploratory factor analysis was employed to identify the underlying factors, whereas confirmatory factor analysis was applied to test the measurement models. The analysis yielded a three-factor TCBM: (1) discrepancy, (2) efficacy and (3) principal support. The results demonstrated a good fit of the model: normed χ 2 = 3.156, Tucker-Lewis Fix Index = .987, Comparative Fix Index = .991 and Root Mean Square Error of Approximation = .048. The results also provided evidence for convergent validity, discriminant validity and construct reliability. The TCBM is an empirically tested model derived in a local Malaysian cultural education setting. It provides direction for practitioners in planning and designing training programmes of change management for school principals in the enhancement of TCB among teachers in schools. Besides, Teacher Change Beliefs Scale is a promising and welcome tool for both practitioners and researchers. With only nine items, it is easy to administer and not time-consuming.